Factors surrounding treatment decisions in non-small cell lung cancer - Morgan, Helen (2024)
Introduction Despite good outcomes from both thoracic surgery and radical radiotherapy, more than 1 in 5 people who appear eligible for curative treatment of lung cancer do not receive any treatment at all. Spotlight data from the National Lung Cancer Audit (NLCA) found 15% of people chose not to receive treatment, rather than for medical reasons. The reasons behind this are unclear and are likely influenced by regional differences as well as personal patient beliefs, which are difficult to capture using quantitative data.